MENINGKATKAN KEMAMPUAN BERHITUNG PERKALIAN SISWA MENGGUNAKAN METODE JARIMATIKA DI KELAS III SDI PLUS IMAM MUSLIM - Nur Izatul Maula; Makhrus Makhrus; Suwanto Suwanto; Fitriani Fitriani (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2024)
The background for conducting this classroom action research was the achievement of student learning outcomes in class IV of Bustan El Firdaus Kawunganten Islamic Elementary School on low number pattern material, so there is a need for learning improvements. The learning improvement plan will be carried out by applying problem-based learning methods in 2 cycles. The sample for this research were 18 students in class IV of Bustan El Firdaus Islamic Elementary School, 10 boy students and 8 girls students. Research started from October to December. At the end of the cycle I showed an increase in the learning outcomes of number pattern material in the pre-cycle. Then in cycle II the learning outcomes obtained also increased significantly compared to cycle I. At the end of cycle II the classical completeness obtained was 94.4% while the indicator of success which was used as a reference in this research was the achievement of classical completeness of 80% so the research had been successful.